Quantifying displacement in urban disaster contexts - Lewis, N; Herwanger, N (Refugee Studies Centre, University of Oxford, 2022)
Disaster risk reduction and humanitarian programming activities to assist displaced populations are more effective when informed by timely, accurate data. There is, however, a significant data gap in the context of urban displacement.